Evolutionary heuristic to determine future land use - Carreno, E. M. [UNESP]; Padilha-Feltrin, A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2008)
In the spatial electric load forecasting, the future land use determination is one of the most important tasks, and one of the most difficult, because of the stochastic nature of the city growth. This paper proposes a fast and efficient algorithm to find out the future land use for the vacant land in the utility service area, using ideas from knowledge extraction and evolutionary algorithms. The methodology was implemented into a full simulation software for spatial electric load forecasting, showing a high rate of success when the results are compared to information gathered from specialists. The importance of this methodology lies in the reduced set of data needed to perform the task and the simplicity for implementation, which is a great plus for most of the electric utilities without specialized tools for this planning activity. © 2008 IEEE.
Keywords: Distribution planning; Knowledge extraction; Land use; Spatial electric load forecasting; Electric load management; Electric loads; Electric tools; Electric utilities; Energy conversion; Evolutionary algorithms; Forecasting; Heuristic programming; Potential energy; Potential energy surfaces; Public utilities; Vibrations (mechanical); 21st century; Efficient algorithms; Electrical energy; High rates; Service areas; Simulation softwares; Specialized tools; Stochastic nature; Electric load forecasting